Comparison of docosahexaenoic acid uptake in murine cardiomyocyte culture and tissue: Significance to physiologically relevant studies. (March 2015) - Lamaziere, Antonin; Richard, Doriane; Bausero, Pedro; Barbe, Ullah; Kefi, Kaouthar; Wolf, Claude; Visioli, Francesco
Abstract: Long-chain n −3 (or omega 3) fatty acids, namely docosahexaenoic acid (DHA, 22:6 n −3) and eicosapentaenoic acid (EPA, 20:5 n −3) have been attributed cardioprotective properties. In this study, we evaluated the incorporation of DHA into cardiomyocytes and the shift in the omega 3/omega 6 ratio after supplementation of primary cardiomyocyte culture. Results are compared with atrial tissue concentrations attained after prolonged feeding of rats. The major difference between in vitro vs. in vivo supplementation is the paradoxical accumulation of arachidonic acid in cultured cardiomyocyte. However, this increase does not give rise to a higher PGE2 production after cellular stimulation, as compared with controls, possibly because of the associated inhibition of sPLA2 by DHA. Notably, in vitro supplementations with DHA 10 to 25 μM approximate in vivo pharmacological treatments.